Revenue Diversification and Banks Funding Costs under Financial Regulation - Jonathan Christian Halim; Clarissa Nathania Putri; Maria Gabriella Tan; Kevin Pratama Santoso (Journal of Economics Business Industry, 2025)
The banking literature suggests that banks can reduce their funding costs by optimising their deposit mix to prioritise low-cost accounts, managing capital efficiently, and employing diversification strategies to attract more cost-effective funding sources. While the roles of deposit mix optimisation and capital management in lowering funding costs are well documented, the impact of diversification remains relatively underexplored, particularly in the Indonesian context. This study examines the relationship between diversification, financial regulations, and banks' funding costs in Indonesia. A sample of 87 commercial banks operating in Indonesia over the period 2010 to 2024 was selected based on the availability of data. This study employs the fixed effects model as the main estimation approach, along with two-stage least squares (2SLS) and generalised method of moments (GMM) estimation techniques for robustness testing. The results indicate that diversification significantly lowers banks' cost of funds in Indonesia. The analysis also reveals that revenue diversification has a more pronounced impact on large and foreign or joint venture banks. Furthermore, the study identifies an indirect effect of financial regulations on banks' funding costs through revenue diversification. The study highlights the need for bank managers, particularly those in large and foreign or joint venture banks, to proactively adopt diversification strategies to optimise their funding structures and reduce costs effectively. The study provides insights into the broader implications of the interactions between regulatory frameworks, bank diversification, and funding costs in Indonesia. revenue diversification; asset diversification; financial regulations; banks' funding costs; Indonesia.